Development of Management Industry of Lawang Oil (Cinnamomum Culilawan Blume) in Ujung Kia Village, Ki District, Boven Digoel Regency, Papua Province - Sebestina Siman; Hendricus Lembang (Universitas Pendidikan Ganesha, 2019)
Lawang oil (cinnamomum culilawan BL) is a commodity from non-timber forest products from Ujungkia Village, Ki District, Boven Digoel Regency. The rich of natural resources can be processed into a commodity to increase local community welfare and local revenue (PAD). So that this study aims to determine the feasibility of developing management industry of lawang oil in Ujungkia Village which will become an industrial center and a new center for economic growth. The type of research used is descriptive qualitative, combined with quantitative research, namely the method of analysis of Loss / Profit Ratio and SWOT. The results of the research are the development of management industry of the lawang oil in Ujungkia Village, Ki District, Boven Digoel Regency which has good and feasible prospects to be realized based on the results of the R/C analysis and SWOT analysis. Based on the R/C ratio analysis that is obtained is equal to 1.585 which means the value of R/C ratio ≥ 1, in this case management industry of Lawang oil activities are profitable. Then the results of the SWOT analysis obtained Total Strength - Total Weakness (S-W) which is 1.86 or X = 1.86. While the difference in Total Opportunities - Total Threats (0-T) is 1.44 or Y = 1.44. This means that (1.86; 1.44) is in Quadrant I (positive, positive).